Assessing the Impact of Asthma: A Cross-Sectional Study in Workers Undergoing Therapy - Omrane, Amira; Krayem, Latifa; Touil, Imen; Romdhani, Raja; Brahem, Yosra; Boussoffara, Leila; Knani, Jalel; Khalfallah, Taoufik; Boudawara, Nadia (La Medicina del Lavoro, 2025)
Background: This study aimed to investigate the impact of asthma on work productivity among adults receiving asthma therapy. Methods: A cross-sectional study involving 101 asthmatic patients treated at the Pulmonology Department of University Hospital in Mahdia (Tunisia) who had been employed for at least six months was conducted over the course of a year. Recruited patients were asked to complete a self-administered questionnaire that consisted of the Simplified Medication Adherence Questionnaire (SMAQ), the Work Productivity and Activity Impairment (WPAI), and the Pichot questionnaire. Results: The study’s participants had a sex ratio of 0.51 and a mean age of 44.1±13.2 years. Exposure to aerocontaminants was high among 64.4% of patients. The majority of the patients were treated with inhaled corticosteroids (ICS) and long-acting beta-agonists (LABA) (54.4%), and nearly half were classified as having moderate asthma. Our findings revealed significant challenges faced by these patients, with 62.4% experiencing poorly controlled or uncontrolled asthma. Additionally, 69.3% were non-adherent to treatment, and 71.3% reported worsening symptoms while at work. They worked an average of 38.3±16.4 hours per week. The impact of general health status on work productivity was measured at 3.3±2.5. Absenteeism and presenteeism rates were 4.2% and 33.1%, respectively, resulting in a productivity loss of 30.4%. Activity impairment was associated with factors such as gender, alcohol consumption, and uncontrolled asthma. Conclusion: Addressing asthma control, working conditions, and mental health emerges as essential strategies to enhance workplace productivity. When evaluating the effectiveness of interventions among active asthmatic patients, presenteeism, absenteeism, and productivity loss should be considered.